2018
DOI: 10.12933/therya-18-513
|View full text |Cite
|
Sign up to set email alerts
|

Home-range analyses and habitat use by white-tailed deer females during the breeding season

Abstract: There is little knowledge about the behavior strategies used by white-tailed deer (Odocoileus virginianus texanus) females with fawns. This study analyzed the variation in home range and the use of vegetation types by eight females during the breeding season in a brushland in northeastern Mexico and compared the strategies of females with and without fawns. Eight females were captured and radiotelemetry collars were fitted to them. We sampled two to three 24-hour cycles at 1-hour intervals monthly from April t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…That is, species that can use different types of habitats and that can be favored in modified landscapes [54]. In addition, some studies have also found no relationship between the richness of medium and largesized mammals and the amount of native habitat [8,21,55,56] or others have recorded a high species richness in landscapes with strong urban [1,58] or agricultural influence [8,49,50]. In this way, species with a wide ecological niche can be favored by these modified landscapes and, probably, maintain their populations in agricultural landscapes [59].…”
Section: Discussionmentioning
confidence: 99%
“…That is, species that can use different types of habitats and that can be favored in modified landscapes [54]. In addition, some studies have also found no relationship between the richness of medium and largesized mammals and the amount of native habitat [8,21,55,56] or others have recorded a high species richness in landscapes with strong urban [1,58] or agricultural influence [8,49,50]. In this way, species with a wide ecological niche can be favored by these modified landscapes and, probably, maintain their populations in agricultural landscapes [59].…”
Section: Discussionmentioning
confidence: 99%
“…In words, landscapes dominated by pastures are predominantly used by generalist species. In addition, some studies have also found no relationship between the richness of medium-and large-sized mammals and the amount of native habitat [8,21,61,62], while others have recorded a high species richness in landscapes with a strong urban [63,64] or agricultural influence [8,44,56]. In this way, species with a wide ecological niche can be favored by these modified landscapes and can, probably, maintain their populations in agricultural landscapes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Entonces, la baja presencia de grupos fecales, principalmente de hembras, en ambas UMA, y el alto grado de segregación espacial en el verano, coincide con la época de pariciones. Las hembras de venado cola blanca muestran patrones de comportamiento complejos durante la preñez y la crianza de los cervatos: probablemente el tipo de áreas utilizadas por las hembras se modifica, así como el forrajeo y las estrategias para evitar a los depredadores buscando áreas con cierta cobertura vegetal de protección (Soto-Werschitz et al, 2018). Así también, Long et al (2005) y Kolodzinski et al (2010) observaron que, en verano, las hembras se dispersaron dada la época de pariciones.…”
Section: Uma/estaciónunclassified